The Dutch slavery and colonization DNA. A call to engage in self-examination - Steinmetz, Carl H. D. (Advances in Social Sciences Research Journal, 2021)
This article answers the question whether there is a Dutch slavery and colonisation DNA. After all, the Netherlands has centuries of experience (approximately three and a half centuries) with colonisation (including occupation, wars and genocide, rearrangement of land and population, plundering and theft), trade in enslaved people (the Atlantic route: Europe, Africa, North and South America) and trade in the products of these enslaved people. The Netherlands has colonised large parts of the world. This was a large part of Asia, including the Indonesian archipelago, Malaysia, Ceylon, Taiwan and New Guinea, large parts of the continent Africa, including Madagascar, Mozambique, Cape of Good Hope, Luanda, Sao Tome, Fort Elmina etc., and North (New York) and South America (including Brazil, Dejima, Surinam and the Netherlands Antilles). It is a fact that human conditions and circumstances influence the human DNA that is passed on to posterity. This goes through the mechanism of methylation. This mechanism is used by cells in the human body to put genes in the "off" position. Human conditions and circumstances are abstractly formulated, poverty, hunger, disasters and wars. These are also horrors that accompanied slavery and colonisation. The Dutch, as slave traders, plantation owners, occupiers of lands, soldiers, merchants, captains and sailors, and administrators and their staff, have had centuries of experience with practising atrocities. Because those experiences are translated into the DNA of posterity, it is understandable that Dutch authorities misbehave towards immigrants and refugees. Those institutions are political leaders, governmental institutions, such as the tax authorities and youth welfare, and also companies that do their utmost to avoid taking on immigrants. This behaviour is called institutional colour and black racism.